Recruitment and management in local government authorities of Tanzania in Masasi district council - Mboyi, Wishega (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University Dar es Salaam Campus College in partial fulfillment of the requirements for the award of the degree of Master of Science in Human Resource Management (MSc-HRM) of Mzumbe University